Epidermal growth factor alters silica nanoparticle uptake and improves gold-nanoparticle-mediated gene silencing in A549 cells - Susnik, Eva; Bazzoni, Amelie; Taladriz-Blanco, Patricia; Balog, Sandor; Moreno-Echeverri, Aura Maria; Glaubitz, Christina; Brito Oliveira, Beatriz; Ferreira, Daniela; Viana Baptista, Pedro; Petri-Fink, Alke; Rothen-Rutishauser, Barbara (Frontiers in Nanotechnology, 2023)
Delivery of therapeutic nanoparticles (NPs) to cancer cells represents a promising approach for biomedical applications. A key challenge for nanotechnology translation from the bench to the bedside is the low amount of administered NPs dose that effectively enters target cells. To improve NPs delivery, several studies proposed NPs conjugation with ligands, which specifically deliver NPs to target cells via receptor binding. One such example is epidermal growth factor (EGF), a peptide involved in cell signaling pathways that control cell division by binding to epidermal growth factor receptor (EGFR). However, very few studies assessed the influence of EGF present in the cell environment, on the cellular uptake of NPs. We tested if the stimulation of EGFR-expressing lung carcinoma cells A549 with EGF affects the uptake of 59 nm and 422 nm silica (SiO2) NPs. Our findings show that EGF binding to its receptor results in receptor autophosphorylation and initiate signaling pathways, leading to enhanced endocytosis of 59 nm SiO2 NPs, but not 422 nm SiO2 NPs. Additionally, we investigated whether the uptake enhancement can be achieved with gold NPs, suitable to downregulate the expression of cancer oncogene c-MYC. We demonstrated an enhanced gold (Au) NPs endocytosis and subsequently a higher downregulation of c-MYC. These findings contribute to a better understanding of NPs uptake in the presence of EGF and that is a promising approach for improved NPs delivery.